Prove that tan^2theta+cot^2theta+2=cosec^2theta sec^2theta.
Answers
Answered by
37
Hope it helps u . then pls mark it as brainliest.
Attachments:
![](https://hi-static.z-dn.net/files/d52/0265bbbb9b66f24617b5b833a0f05a02.jpg)
Answered by
22
Answer:
tan^2θ + cot^2θ + 2 = sec^2θ . cosec^2θ
L.H.S
Sin^4θ+cos^4θ+2sin^2θcos^2θ/sin^2θcos^2θ
(Sinθ+cosθ^2)2/sin^2θcos^2θ
=(1)2/sin^2θcos^2θ
Cosec^2θsec^2θ
RHS=Cosec^2θsec^2θ
LHS=RHS
Similar questions
Political Science,
9 months ago
Science,
9 months ago
Math,
9 months ago
Math,
1 year ago
Biology,
1 year ago